Peran Orang Tua di Dalam Membangun Kepercayaan Diri Anak Sejak Dini: The Role of Parents In Building Children’s Confidence From an Early Age - Anisa Sabila Nababan; Fenty Zahara Nasution (Psikologi Prima, 2022)
During the development of children who are still at an early age, parents must pay more serious attention to children, because the developmental period of early childhood is a period that is easy to shape personality in child development. The purpose of this study was to build self-confidence in children who are in the developmental stage. A child's self-confidence can be built by parents in various ways, this method can be done in daily life in carrying out activities with children such as being a good listener to children, showing respect, providing opportunities for children to help, listening to children's opinions, train children's independence, give praise to children when doing good, help children be more optimistic, cultivate children's interests and talents, invite children to solve problems, give children opportunities to play together with their friends. The method used in this study is a qualitative method using literature studies, information obtained from existing studies or previous research.